Self Adaptation Programme helps new UMPSA students adjust at university - Rahimah, Mohamed (UMPSA, 2024)
PEKAN, 17 August 2024 – A total of 100 new 2024/2025 diploma students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in the Self Adaption Programme organised by Pusat Sejahtera, Student Affairs and Alumni Department (JHEPA).